Application of the Ergo-Office ROSA Method to Assess Work Posture Risks in MSME Workers in South Sumatra Province: Implications for Occupational Health - Setiawan, Heri; Susanto, Sani; Rinamurti, Micheline; Alfian, Achmad; Pratama, Yohanes Dicka; Budiarto, Dominikus (Jurnal Medisci, 2025)
Background: Computers are the main devices that support the efficiency and effectiveness of work in modern office environments, including MSMEs in South Sumatra Province. However, long-term use of computers with unergonomic sitting postures can increase the risk of Work-Related Musculoskeletal Disorders (WMSDs) in workers. The results of preliminary observations showed that the percentage of variation in WMSD complaints was between 13%-42% of the total work-related diseases related to computers. Aim: This study aims to identify muscle complaints experienced by workers, analyze the risk of working posture using ergonomic methods, and provide suggestions for improvements to minimize the risk of musculoskeletal disorders. Methods: This study uses the Rapid Office Strain Assessment (ROSA) method to assess the risk of computerized and sitting activity-based work postures. In addition, Nordic Body Map was used to map the location of muscle complaints in respondents. The study was conducted on 20 workers in four MSMEs in South Sumatra Province who worked with high computer intensity. Results: The analysis showed that all four respondents had a high level of occupational posture risk based on the ROSA score. A total of 36 muscle complaints were reported, with the most complaints located in the lower neck, waist, and buttocks. The main factors causing complaints include prolonged static sitting positions and inadequate adjustment of work facilities. Conclusions: The work posture of MSME workers in South Sumatra Province indicates a level of ergonomic risks that requires serious attention. Interventions such as improving work facilities and training in correct work posture are highly recommended. Implementation. These findings affirm the importance of applying ergonomic principles in computer-based work environments to prevent WMSDs, improve work comfort, and support the productivity of government sector workers.